Biological Treatments and Target Therapies for Pediatric Respiratory Medicine: Not Only Asthma - Ghirardo, Sergio; Mazzolai, Michele; Di Marco, Antonio; Petreschi, Francesca; Ullmann, Nicola; Ciofi degli Atti, Marta Lucia; Cutrera, Renato (Frontiers in Pediatrics, 2022)
We present a description of pediatric pneumology biological medications and other target therapies. The article aims at introducing the importance of a molecular approach to improve treatments. The first item treated was T2-High asthma and its current biological treatment and prescribing indications to propose a flow-chart to guide the clinical choice. Molecular rationales of such treatments are used to introduce a more general description of the biological and molecular approach to target therapies application. We introduce a general interpretation approach to neutrophilic asthma using the molecular plausibility one in order to propose possible future treatments mainly targeting interleukin-1 (IL-1), IL-17, IL-12, and IL-23. Indeed, cytokines can be excellent targets for several biological treatments. Downregulation of specific cytokines can be crucial in treating autoinflammatory and rheumatological diseases with a pulmonary involvement. Such conditions, although rare, should be early recognized as they can involve significant improvement with a properly targeted therapy. We face these conditions in a cherry-picking fashion picturing SAVI (STING-associated vasculopathy with onset in infancy), CANDLE (chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature), and COPA (coat proteins alpha syndrome) syndrome pulmonary involvement. Such examples are functional to introduce molecular-based approach for patients with rare conditions. Molecular plausibility can be highly valuable in treating patients with not-approved but possibly highly effective therapies. Due to the rarity of these conditions, we stress the concept of basket trials using the example of cytokinin-directed immunosuppressive treatment. Lastly, we provide an example of augmentative therapy using the alpha1 antitrypsin deficiency as a model. In summary, the article presents a collection of the most recent achievements and some possible future developments of target therapies for pediatric pulmonary conditions.